A new calculation method for the free electron fraction of an ionization chamber in the ultra-high-dose-per-pulse regimen. (November 2022) - Di Martino, Fabio; Del Sarto, Damiano; Barone, Salvatore; Giuseppina Bisogni, Maria; Capaccioli, Simone; Galante, Federica; Gasparini, Alessia; Mariani, Giulia; Masturzo, Luigi; Montefiori, Marco; Pacitti, Matteo; Paiar, Fabiola; et al.
Highlights: The free-electrons-fraction is the fraction of the electrons generated that are collected without attachment. The method proposed is based only from measure of charge collected varying the voltage applied. The method proposed can be use in the commissioning phase of a dedicated to the Flash radiotherapy Linac. Abstract: The free electron fraction is the fraction of electrons, produced inside the cavity of an ionization chamber after irradiation, which does not bind to gas molecules and thereby reaches the electrode as free electrons. It is a fundamental quantity to describe the recombination processes of an ionization chamber, as it generates a gap of positive charges compared to negative ones, which certainly will not undergo recombination. The free electron fraction depends on the specific chamber geometry, the polarizing applied voltage and the gas thermodynamic properties. Therefore, it is necessary to evaluate such fraction in an accurate and easy way for any measurement condition. In this paper, a simple and direct method for evaluating the free electron fraction of ionization chambers is proposed. We first model the capture process of the electrons produced inside an ionization chamber after the beam pulse; then we present a method to evaluate the free electron fraction based on simple measurements of collected charge, by varying the applied voltage. Finally, the results obtained using an Advanced Markus chamber irradiated with a Flash Radiotherapy dedicated research Linac (ElectronFlash) to estimate the free electron fraction are presented. The proposed method allows the use of a conventional ionization chamber for measurements in ultra-high-dose- per -pulse (UHDP) conditions, up to values of dose- per -pulse at which the perturbation of the electric field due to the generated charge can be considered negligible.